Effects of the Style of Teaching and Emotional Intelligence on Learning Outcomes Dribbling in Basketball Games - Hamonangan, Hamonangan (Jurnal Primagraha, 2021)
This study aims to determine the effects the style of teaching and emotional intelligence the results of dribbling in the game of basketball In addition, research also aims to determine the effect of motivation on both the teaching style. Teaching style in this study is the inclusion of teaching styles and self check style, and emotional intelligence to learn the emotional intelligence to learn high and low emotional intelligence. Research conducted at the MAN1 Medan academic year 2014/2015. The research method is an experiment with a 2x2 ftreatment by level design with sample size of 52 people. The results of this study are as follows:(1) overall there is a difference between teaching styles Inclusion and teaching styles Self Chek of dribbling in basketball games learning outcomes, (2) for students who have high emotional intellegence to learn, giving Inclusion teaching style to give a better effect than Self Check teaching style on learning outcomes dribbling in basketball games, (3) for students who have low emotional intellegence ,the provision of Self Check teaching style to give a better effect than the Inclusion of teaching styles to learning the dribbling in basketball games, and (4) there is interaction between the teaching style with emotional intelligence towards learning outcomes dribbling in basketball games.